PENERAPAN METODE ACTIVE LEARNING TIPE TEAM QUIZ BERBANTUAN APLIKASI KAHOOT DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPS 3 DI SMA NEGERI 1 NARMADA - Erik, Septi Hariadi; Ni Made Novi Suryanti; Suud; Masyhuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the learning outcomes of students in grade XI IPS 3 SMA Negeri 1 Narmada by applying a team quiz-type active learning method assisted by a kahoot application. This learning is a class action research (PTK) that lasts for 2 cycles, each cycle consists of 4 stages, namely planning, implementation, observation, and evaluation. One cycle is carried out 3 times. The results of this study can be concluded that the active learning method of team quiz type assisted by kahoot application in cycle I was implemented by 80% and in cycle II it was carried out by 100% so that there was an increase of 20%. This has an impact on the level of completeness of student learning outcomes, which was initially in the first cycle of 52.8%, increased in the second cycle to 77.8%, surpassing the performance indicator of 75% of students achieving KKTP 75. This means that the application of the team quiz type active learning learning method assisted by the kahoot application can improve student learning outcomes in class XI IPS 3 in sociology subjects at SMA NEGERI 1 Narmada.